Chlamydia infection in individuals reporting contact with sexual partners with chlamydia: a cross-sectional study of sexual health clinic attendees. (8th June 2015) - Huffam, Sarah; Chow, Eric P F; Fairley, Christopher K; Hocking, Jane; Peel, Joanne; Chen, Marcus
Abstract : Objectives: We aimed to ascertain the proportion of positive, and predictive factors of chlamydia infection among females, heterosexual males and men who have sex with men (MSM) presenting to a sexual health service reporting contact with a chlamydia infected sexual partner. Methods: A cross-sectional analysis of patients attending the Melbourne Sexual Health Centre from October 2010 to September 2013. Behavioural data obtained using computer assisted self-interview were analysed to determine factors predictive of chlamydia. Results: Of the 491 female, 808 heterosexual male, and 268 MSM chlamydia contacts, the proportion diagnosed with chlamydia were 39.9% (95% CI 35.7% to 44.3%), 36.1% (95% CI 32.9% to 39.9%) and 23.5% (95% CI 18.8% to 29.0%), respectively. Female chlamydia contacts were more likely to have chlamydia if age <25 (adjusted OR (AOR) 1.86, 95% CI 1.12 to 3.10) or if they reported inconsistent condom use during vaginal sex with a regular male partner (AOR 2.5, 95% CI 1.12 to 6.14). Heterosexual male contacts were more likely to have chlamydia if age <25 (AOR 1.69, 95% CI 1.25 to 2.28) or if they had a regular female sexual partner (AOR 1.38, 95% CI 1.03 to 1.85). In MSM urethral chlamydia was diagnosed in 8.8%, rectal chlamydia in 20.2%, and 3.9% at both sites. MSM were more likely to have chlamydia if they had a regular male sexual partner (OR 2.12, 95% CI 1.18 to 3.81). Conclusions: This study of female, heterosexual male, and MSM presentations with self-reported chlamydia contact provides insight into the likelihood and predictive factors of infection. The data may inform policy and individual clinical decision making regarding presumptive treatment of chlamydia contacts.